TIME-DEPENDENT EXPRESSION OF IL-1Î² mRNA - A PRELIMINARY STUDY FOR POSSIBLE WOUND AGE MARKER - Bitoljanu, Natasha; Ivcheva, Ana; Srpanova, Viktorija Belakaposka; Cakar, Ljupco; Siamkouri, Rosica; Stankov, Aleksandar; Pavlovski, Goran; Risteski, Sasho; Jakovski, Zlatko (Journal of Morphological Sciences; Vol 6 No 1 (2023): JMS, 2023)
Accurate estimation of wound age is a very important task in forensic medicine field, because it can helps in reconstruction of crime scene. IL-1Î² is proinflamatory cytokine and plays a major role in wound healing process. The aim of the study is to develop a method for the reliable estimation of dermal injury age. In this study the expression of IL-1Î² mRNA was evaluated by real-time PCR at skin human wounds with different post-injuried period. We collected 27 human skin wound samples from forensic autopsy cases at our Institute. In our study were include samples from lacerations, incised wounds and stab wounds, with a known time of injury and death. Wound samples were divided into five groups: control group (n=5); first group consisted of cases with immediate death (n=7); second group consisted of cases with survival from 1 hour to 6 hours (n=5); the third group comprised cases with survival from 6 hours to 72 hours (n=3); the fourth group comprised cases with survival from 72 hours to 168 hours (n=7). In this study we detected increased expression levels of IL-1 Î² mRNA in the second group with survival time from 1 to 6 hours. Keywords: IL-1Î²; wound age; Real-time PCR; autopsy cases; human dermal injuries. https://doi.org/10.55302/JMS2361121b